2006
DOI: 10.1542/peds.2006-0148
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine Adjunctive Therapy Among Children and Adolescents With Primary Generalized Tonic-Clonic Seizures

Abstract: Adjunctive lamotrigine therapy seems effective in controlling primary generalized tonic-clonic seizures among patients 2 to 20 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…Brodie et al 12 reported that those patients with idiopatic GTC seizures had a better response to treament than those with partial seizures (with or without secondary generalization). Trevathan et al 16 reported the same good control of primary tonic-clonic generalized seizure, in a subgroup of 14 children age 2 to 20 years old of a randomized clinical trial, but they were also on 1 or 2 concurrent anti epileptic drugs (AEds). In our study we also noticed that patients with generalized tonic clonic seizures had a more satisfactory control.…”
Section: Resultsmentioning
confidence: 96%
“…Brodie et al 12 reported that those patients with idiopatic GTC seizures had a better response to treament than those with partial seizures (with or without secondary generalization). Trevathan et al 16 reported the same good control of primary tonic-clonic generalized seizure, in a subgroup of 14 children age 2 to 20 years old of a randomized clinical trial, but they were also on 1 or 2 concurrent anti epileptic drugs (AEds). In our study we also noticed that patients with generalized tonic clonic seizures had a more satisfactory control.…”
Section: Resultsmentioning
confidence: 96%
“…Its main disadvantage is the slow titration rate needed to avoid skin rashes; the titration must be even slower if LTG is used with valproate. 27 Lamotrigine was first synthesized in the 1970s based on the observations that many existing AEDs were folic acid antagonists 28 ; however, LTG has very little folic acid antagonism. Although the precise mechanism of action of LTG is unknown, a proposed mechanism is a use-dependent blocking effect on voltage-sensitive sodium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Two good examples in developmental psychopharmacology would be drugs such as clozapine and lamotrigine. The use of these two drugs is much less controversial because they have been shown to be efficacious for conditions such as treatmentrefractory schizophrenia and epilepsy in paediatric patients (Sporn et al, 2007;Trevathan et al, 2006).…”
Section: Efficacymentioning
confidence: 99%
“…We should take advantage of the new regulatory agency laws (FDA Pediatric Research Equity Act of 2003and EMA regulations 1901/2006and 1902/2006) that are creating huge data sets of clinical and treatment data from the large numbers of clinical trials that are being conducted (Stoyanova-Beninska et al, 2011). For instance the new EU paediatric regulation forces the drug industry to conduct clinical trials with paediatric populations before a licence is granted for adult populations.…”
Section: The Future Of Developmental Neuropsychopharmacologymentioning
confidence: 99%